Size and shape dependent order–disorder phase transition of Co–Pt nanowires - Qi, Weihong (2013)
Monte Carlo simulation of the order–disorder transition revealed that the transition temperature of Co–Pt nanowires increases with wire diameter, approaching the bulk value if the size is large enough. The transition temperature is affected by the shape of cross-section, though the shape effect is less significant than the size effect. It is showed that the rise of transition temperature in nanowires is largely due to the decrease of surface area compared with nanoparticles. The phase separation and tetragonalization are discussed by introducing mixing parameter and asphericity parameter. It is also found that the order–disorder transition starts from the surface and then to the core, indicating that the order–disorder transition of nanowires is a surface-dominant phenomenon, governed by the atomic under coordination.